Development, gut health, and longevity of European bee on the provision of biosugar syrup. (January 2023) - Hasan, Ali; Iqbal Qazi, Javed; Tabssum, Fouzia; Hussain, Ali
Abstract: Syrup containing monomeric sugars was prepared from banana-peel waste by hydrolyzing it with cellulose as well as pectinase to feed honeybees instead of using sucrose syrup in the period when there is no nectar in flowers. This syrup was provided to the caged workers with and without the addition of monomeric sugars (glucose, fructose) for a period of two weeks. It was observed that worker bees belonging to experiment No. 2 (pollens + 25% w/v glucose in BPW sugar syrup) had a significant increase in longevity. In addition to this, morphometric and histological analyses were also done. Morphometric studies confirmed reasonable increases in different body parameters of worker bees. Their hypopharyngeal gland became developed with a mean acinal surface value of 0.019 ± 0.0 mm 2 as compared to the control's 0.0124 ± 0.0 mm 2 . Sections of the midgut (stomach) and small intestine up to 8 μm were prepared and observed under camera fitted microscope. Bees of experiment No. 2 had peritrophic membranes in close contact with rabdorium-like control bee's midgut, nuclei stained hyper chromatic, considerable increase in gastric cells discharging, and compact and homogeneous mass of semi-digested pollens in the central part of the intestinal lumen which indicates the improved digestion. The mean midgut lumen diameter was 450 ± 34.6 μm 2 as compared to the control's 240.0 ± 30.5 μm 2 and the mean intestinal lumen diameter was 223.3 ± 33.3 μm 2 as compared to the control's 113.3 ± 38.4 μm 2 which is an indication of tissue development. In the end, it is concluded that the use of biosugar syrup is good alternative to sucrose sugar syrup for honeybees. Graphical abstract: Fate of enzyme treated BPW. Image 1 Highlights: Apis mellifera Caged workers were fed with biosugar syrup made by banana peels, with and without the addition of monomeric sugars. Provision of biosugar syrup resulted in developed hypopharyngeal gland, increase in gastric cells and peritrophic membranes. Increases in lumen diameter of midgut and intestine and slight vacuolation of columnar epithelial cells were also observed.